THE OVERDEPENDENCE OF AFRICAN COURTS AND BUSINESSES ON ENGLISH LAW AND FORUM: THE NEGATIVE REPERCUSSIONS ON THE DEVELOPMENT OF AFRICAN LEGAL AND ECONOMIC SYSTEMS - Iheme, Williams Chima (Pravni zapisi, 2024)
The uncritical transplantation of English law by Anglophone-African legislators and judges, and their failure to sufficiently adapt English legal concepts to suit the idiosyncratic socioeconomic conditions in Africa, arguably contribute to the perpetuation of English law’s hegemony therein. It is argued that the overdependence on English law and courts by African businesses in resolving contractual disputes is not necessarily due to any alleged stellar qualities of the former, but largely due to the over-marketing of the English legal system’s competence by its apologists. The analysis uses piquant examples to elicit some adverse effects of using/overreliance on the English law and forum by African businesses in resolving contractual disputes. To reposition from the lengthened shadow of English law, Anglophone African legislators, judges and legal scholars, must craft autochthonous legal processes that suit Africa’s tastes and socioeconomic milieu.